2013
DOI: 10.1159/000350875
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Navigation Surgery in Patients with Early Gastric Cancer

Abstract: Clinical application of sentinel node (SN) mapping in patients with early gastric cancer has been a controversial issue for years. However, a recent meta-analysis and a prospective multicenter trial of SN mapping for early gastric cancer have shown acceptable SN detection rates and accuracy of determination of lymph node status. A dual-tracer method that utilizes radioactive colloids and blue dyes is currently considered the most reliable method for the stable detection of SNs in patients with early gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
0
36
0
2
Order By: Relevance
“…An important issue is whether the lymphatic flow from the primary tumor to the original SN(s) changes after EMR/ESD. Our preliminary study showed that the sentinel lymphatic basin was not markedly affected by previous EMR/ESD [26,27]. Modified gastrectomy based on the SN distribution and metastatic status may be feasible, even for patients who underwent EMR/ESD before surgery.…”
Section: Clinical Application Of Laparoscopic Sn Mapping In Early Gasmentioning
confidence: 76%
See 1 more Smart Citation
“…An important issue is whether the lymphatic flow from the primary tumor to the original SN(s) changes after EMR/ESD. Our preliminary study showed that the sentinel lymphatic basin was not markedly affected by previous EMR/ESD [26,27]. Modified gastrectomy based on the SN distribution and metastatic status may be feasible, even for patients who underwent EMR/ESD before surgery.…”
Section: Clinical Application Of Laparoscopic Sn Mapping In Early Gasmentioning
confidence: 76%
“…Theoretically, if the SN(s) is/are pathologically negative for cancer metastasis, EMR/ESD may be sufficient for the curative resection of cT1 gastric cancer beyond the EMR criteria (Fig. 2d) [26,27]. However, further studies are required to verify the safety and effectiveness of combined treatments involving laparoscopic SN biopsy and EMR/ESD.…”
Section: Clinical Application Of Laparoscopic Sn Mapping In Early Gasmentioning
confidence: 99%
“…As the standard surgical treatment in colorectal cancer, intestinal resection and regional lymphadenectomy, including feeding arteries, is considered essential (13,14). In GBC up to stage IIa, the frequency of lymph node metastasis in the pericholedochal area has been reported to be higher compared to that of lymph node metastasis around the hepatic artery (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…From the present study, the right route is considered part of the route of the eRHA. To completely remove the lymphatic basin in the eRHA route, resection of the nodes in the pericholedochal area, posterosuperior pancreaticoduodenal area and retroportal area should also be performed (14). This consideration is undoubtedly a key reason as to why the addition of PD is associated with improved prognosis for patients with GBC (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it remains controversial whether SN mapping would be feasible after ESD because the lymphatic flow from the primary tumor site where ESD is performed remains unknown. However, a previous study suggested that at least the SN basin was not markedly changed in patients who underwent ESD prior to surgery [29,30]. Regarding the combination treatment of ESD and SN biopsy, further studies are required to confirm safety and efficacy.…”
Section: Present Status and Future Prospects Of Sn Navigation Surgerymentioning
confidence: 97%